Selection of the best solar photovoltaic (PV) for Oman. (August 2019) - Abdul-Wahab, Sabah; Charabi, Yassine; Al-Mahruqi, Abdul Majeed; Osman, Isra; Osman, Selma
Highlights: The best type of PV for Oman was found to be Ingeteam 1164 kVA with generic PV. The use of solar system will avoid the emission of large quantities of pollutants. The use of PV has a lower cost of energy compared to the other energy systems. The best location for the utilization of solar energy in Oman is Marmul. The least attractive location for the utilization of solar energy in Oman is Sur. Abstract: Fossil fuel combustion produces about three-quarters of the world's energy supply. However, burning these fuels produces a considerable amount of pollutants, which eventually will harm the environment. The objective of this study is to employ Hybrid Optimization Model for Electric Renewable (HOMER) to find the best photovoltaic system (PV) for Oman's conditions and to analyze the costs and the resulting polluting emissions, which might avoided by using a PV system in place of natural gas and diesel systems. Using HOMER will help determine the best locations in Oman to maximize solar energy production. HOMER simulation results showed that the best type of PV for Oman was Ingeteam 1164 kVA with generic PV. The use of a PV system instead of natural gas and diesel systems will avoid the generation of about 9728892.115 and 13148128.5 kg/year of pollutants, respectively, and will reduce the cost of energy to USD$ 0.085/kWh. The best locations found for using solar energy were Marmul followed by Fahud, Sohar and Qairoon Hairiti due to their low costs of electricity (0.0763, 0.0855, 0.0862 and 0.0869 USD$/kWh, respectively), high solar radiation and clearness index.